IUTAM Symposium on Microstructure-Property Interactions in Composite Materials - IUTAM Symposium on Microstructure-Property Interactions in Composite Materials (1994 : Alborg, Denmark); Pyrz, Ryszard; International Union of Theoretical and Applied Mechanics (Dordrecht : Kluwer Academic Publishers, 1995)
09